INOVASI IoT pH TANAH UNTUK EDUKASI PENGETAHUAN PENGELOLAAN SAWAH DI DESA SINDANGWANGI - Nurul Mega Saraswati; Rizki Noor Prasetyono; Fadly Haris Arsiandro; Siti Khalwa Rakhmawati; Anggraeni Mashinta Sulistyani (Jurnal AbdiMas Nusa Mandiri, 2026)
Efforts to strengthen food security in Sindangwangi Village still face challenges in land management, particularly related to improper soil pH levels that affect soil fertility and crop yields. This community service activity contributed by introducing an Internet of Things (IoT)–based soil pH monitoring device as an educational tool and a decision-support instrument for rice field management. A participatory approach was applied through training sessions, equipment demonstrations, and direct assistance to farmer groups, including sensor installation, real-time data reading via a mobile application, and interpretation of measurement results for land management practices. The evaluation results showed a significant improvement in farmers’ understanding, indicated by an increase in the average score from 39% in the pre-test to 83% in the post-test, with an N-Gain value of 0.71. These findings confirm that the implementation of IoT technology in soil pH monitoring effectively enhances farmers’ knowledge and skills. This initiative not only introduced agricultural technological innovation but also supported more precise, efficient, and sustainable rice field management in the context of village food security.